2001
DOI: 10.1046/j.1365-3083.2001.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Depressed Percentage of CD27+ (Memory) B Cells among Peripheral Blood B Cells in Patients with Primary Sjögren's Syndrome

Abstract: CD27 has been found to be expressed on somatically mutated B cells and is thus a positive marker for memory B cells in peripheral blood (PB). Since abnormal immunogloblin (Ig) production is characteristic of the autoimmune diseases primary Sjögren's syndrome (pSS) and rheumatoid arthritis (RA), we have analyzed in detail the CD27 expression on PB B cell from these patient groups. Staining of PB B cells with monoclonal antibodies (MoAb) specific for CD19 and CD27 revealed a significantly depressed percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
53
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 43 publications
12
53
0
Order By: Relevance
“…Recent studies have shown disturbances in peripheral B cell populations in primary SS, with significantly enhanced CD27Ϫ naive and diminished CD27ϩ memory B cells (6,8,9). This was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recent studies have shown disturbances in peripheral B cell populations in primary SS, with significantly enhanced CD27Ϫ naive and diminished CD27ϩ memory B cells (6,8,9). This was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of peripheral CD27ϩ,CD19ϩ memory B cells was significantly reduced in patients with primary SS compared with healthy control subjects (mean Ϯ SD 13.3 Ϯ 12.3% versus 25.6 Ϯ 7.2%; P Յ 0.0014), whereas the frequency of CD19ϩ,CD27Ϫ naive B cells was significantly enhanced in patients with primary SS (mean Ϯ SD 86.1 Ϯ 12.0% versus 74.4 Ϯ 7.2%; P Յ 0.0014) as reported previously (6,8,9). To ensure that these alterations in patients with primary SS did not further influence the analyses, either CD19ϩ,CD27Ϫ or CD19ϩ,CD27ϩ B cells were gated, and the chemokine receptor expression was subsequently analyzed within each subpopulation ( Figures 1A and B).…”
Section: Chemokine Receptors On B Cells In Primary Ss 2111supporting
confidence: 83%
See 1 more Smart Citation
“…We recognized that power was reduced by dichotomizing variables. However, even with this conservative approach, the results are striking.Third, they raise the possibility that, despite the fact that we found no ethnic difference in CRP concentrations (median 3 mg/liter [interquartile range [3][4][5][6][7] in Caucasians compared with 4 mg/liter [interquartile range 3-7] in nonCaucasians; P ϭ 0.20), our finding of higher CRP concentrations in obese patients could merely reflect a greater proportion of non-Caucasians in the overweight and obese groups, because some studies have shown higher concentrations of CRP in African Americans. This is not the case; when race (categorized as Caucasian and non-Caucasian) was included in the model, the association between BMI and CRP remained significant (P Ͻ 0.001 for the unadjusted and all adjusted models).…”
mentioning
confidence: 74%
“…First, it is well established, by us in our article cited above and by others, that CXCR3 is differentially expressed on CD27Ϫ naive and CD27ϩ memory B cells (1,2). Second, the proportion of CD27Ϫ naive and CD27ϩ memory B cells may vary significantly between healthy controls and patients with several rheumatic disorders (e.g., primary SS [3,4], systemic lupus erythematosus [5]) as well as between disease entities (e.g., primary SS versus RA [3]). In particular, differences in both absolute numbers and frequencies of CD27ϩ B cells have been reported for patients with primary SS (3,4) Effect of folic acid supplementation on the efficacy of methotrexate treatment in rheumatoid arthritis: comment on the article by Khanna et al…”
Section: To the Editormentioning
confidence: 99%